[INVITED] Ultrafast laser photoinscription of large-mode-area waveguiding structures in bulk dielectrics: Invited paper for the section : Hot topics in Ultrafast Lasers. (June 2016) - Stoian, R.; D'Amico, C.; Bhuyan, M.K.; Cheng, G.
Abstract: Ultrafast laser photoinscription and laser-based refractive index engineering develop towards a unique way for three-dimensional optical design inside bulk materials for the conception of embedded photonic applications. The specific optical functions for the light guiding elements, notably their single mode characteristics and the accessible spectral domains, depend on the achieved refractive index contrast in the material transparency window and on the characteristic dimensions of the optical modification. We give here an overview of several laser processing options, developed to increase the effective index area and contrast using pulse engineering methods in space and time, and optical design involving focal shaping, tubular concepts, evanescently coupled waveguide arrays, or structured waveguides. Abstract : Highlights: We give an overview of 3D laser processing techniques in photonics relying on beam engineering. We emphasizing the potential of spatio-temporal beam manipulation for large-mode-area guiding. The design involves focal shaping, tubular concepts, evanescent arrays or structured waveguides.